Pengaruh Pemberian Static Stretching Dan Efflaurage Massage Terhadap Penurunan Nyeri Leher Myofascial Pain Syndrome M. Upper Trapezius - Maimunah, Catur, Isnaini Herawati, S.Fis, M.Sc (2017)
Background: Musculoskeletal pain in the neck is a public health problem interfere with daily activities. Myofascial pain syndrome m. upper trapezius is interference with the presence of trigger point pain arising from a link bands that form muscle fibers such as braided roper when, pressed or palpation cause a local response. Disturbances in because the upper trapezius muscle type I (tonic) and server stabilizers or maintain head posture with muscle working mechanism with slow response, the long latency period so that i can adaptation to the contraction in length or longer. Objective: To determine the effects of static stretching and efflaurage massage to decrease neck pain myofascial pain syndrome m. upper trapezius. Methods: This study is a quasi experimental research design "Pre test and Post test With Control Group Design". The treatment group was given static stretching and massage efflaurage while the control group was given counterpain. The number of respondents in this study were 20 people with purposive sampling technique sampling by considering the inclusion and exclusion criteria. The research was carried out 2 weeks with a frequency of 4x/ week. Results: Based on the Wilcoxon test on static stretching and efflaurage massage obtained value of p = 0.005treatment group and the control group obtained value of p = 0.102. The result of different influences with Mann Whitney test obtained by value p = 0.000. Conclusion: Static stretching and efflaurage massagep roven to reduce pain myofascial pain syndrome m. upper trapezius significant influence on the awarding counterpain there is no significant effect.